2015
DOI: 10.1088/2053-1583/2/3/035019
|View full text |Cite
|
Sign up to set email alerts
|

Phase stability of transition metal dichalcogenide by competing ligand field stabilization and charge density wave

Abstract: Transition metal dichalcogenides (TMDs) have been investigated extensively for potential application as device materials in recent years. TMDs are found to be stable in trigonal prismatic (H), octahedral (T), or distorted octahedral (Td) coordination of the transition metal. However, the detailed understanding of stabilities of TMDs in a particular phase is lacking. In this work, the detailed TMD phase stability using first-principles calculations based on density functional theory (DFT) has been investigated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 41 publications
4
17
0
Order By: Relevance
“…The structure has $0.075 eV lower energy per formula unit than the H structure, which is consistent with the earlier reported value. 8 The H phase of the compound is a semiconductor while the T d phase is semimetallic. The ground state properties of both phases are listed in Table I.…”
Section: A Stability Of Wtementioning
confidence: 99%
See 1 more Smart Citation
“…The structure has $0.075 eV lower energy per formula unit than the H structure, which is consistent with the earlier reported value. 8 The H phase of the compound is a semiconductor while the T d phase is semimetallic. The ground state properties of both phases are listed in Table I.…”
Section: A Stability Of Wtementioning
confidence: 99%
“…6,7 The stability of these phases is explained by the competing effects between ligand field splitting of the d-orbitals energy levels of the transition metals and the charge density wave instability together with structural phase transition. 8 Although the atoms which form WTe 2 are located in the same row of the periodic table as the compounds with Hphase as their ground state, the ground state of WTe 2 is the T d structure. This difference in the geometric structure separates WTe 2 from these H-phase compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Among the recently synthesized groups of layered materials are the transition metal trichalcogenides (TMTCs) which have a chemical formula MX 3 , where M stands for a transition metal from group IV, V, or VI in the periodic table (e.g., Ti, Zr, or Nb) and X is a chalcogen atom (e.g., S, Se, or Te). TMTCs are a much less explored class of materials when compared with the extensively studied transition metal dichalcogenides (TMDCs), which are considered promising candidates for a next generation of flexible nanoelectronic devices due to their wide range of different properties [3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…14,[16][17][18][19][20][21] The transformation from H to T' phase has also been attributed to electron transfer from Au or Ag substrate. 22 The calculations 13,15,[23][24][25][26][27] showed that the T'-phase becomes energetically favorable over H-phase when the system is strongly n-type doped, which naturally occurs under alkali metal intercalation. Calculations with Li/Na adsorption demonstrated that about 0.4…”
mentioning
confidence: 99%